Unveiling the Effects of Stressors on Task Performance: The Role of Thriving at Work and Resilience - Hussain, Zahid; Farid, Hasan; Liu, Xinran; Abbass Shaheen, Wasim (Frontiers in Psychology, 2022)
The current study unveils the effects of stressors on employees’ task performance through the mediating role of thriving at work and a moderating role of resilience grounding on conservation of resources theory. The analysis of collected data from 331 supervisor-employee dyads in the hospitality sector of China explicates that role conflict and perceived workload have a negative influence on thriving at work and thriving has a positive relationship with task performance. The results corroborate the mediating role of thriving at work between role conflict, perceived workload and task performance. Further, the resilience suppressed the negative relationship between role conflict, perceived workload and thriving at work. Moreover, our study underscores the theoretical and practical contributions regarding the negative influence of stressors on thriving at work and by exhibiting the importance of conservation of resources mechanism for employees’ behavioral outcomes.